Peran Gender Sebagai Group Pada Kepemimpinan Path Goal Dan Motivasi Sebagai Determinan Kinerja Guru - Ni Made Satya Utami; I Made Purba Astakoni (UNHI Press, 2020)
The objectives of this study are: 1) analyzing and explaining the influence of leadership on the path-goal model on teacher performance, 2) analyzing and explaining the effect of work motivation on teacher performance, 3) testing the role of gender as a group in the teacher performance determination model. The population in this study is 43 public elementary schools in Denpasar, Kota Denpasar. Samples were taken as many as 4 elementary schools which are expected to represent the population with 80 respondents interviewed by teachers and education personnel. The analysis technique uses the Partial Least Square (PLS) approach. Based on the analysis results it can be explained that; the first hypothesis testing results obtained that the path-goal leadership has a positive effect on teacher performance, with a coefficient of 0.097 and a t-statistic of 0.364 (t-statistic 0.364 <1.96) or a p-value of 0.176 (> 0.05), meaning a hypothesis 1 is not acceptable. In testing the second hypothesis, it is found that work motivation has a positive effect on teacher performance with a coefficient value of 0.099 and a p-statistic of 0.340 (p-statistics of 0.340 <1.96) or a p-value of 0.734 (> 0.05), that means the hypothesis 2 is not acceptable. The role of women's gender through the construct of leadership to teacher performance is greater than male gender. While male gender through the construct of motivation towards teacher performance is greater than female gender.